Can Executive Academic Experience Help Companies Improve Their Innovation? Empirical Study of Chinese Listed It Companies - Zeng, Hongjun (International Journal of Business and Management Future, 2020)
In recent years, as the largest emerging market, China's economic development has gradually shifted from the high growth stage to the high-quality development stage. Company is an essential micro-subject of macroeconomic activities, and an entrepreneur's academic background is a critical factor in achieving high-quality corporate development. This study takes the data of IT listed companies in China from 2012 to 2017 as the sample, Screening research samples based on academic experience requirements based on requirements for current or former teaching and research positions in universities, then makes an empirical analysis on the connection between academic executives and companies innovation ability. The results indicate that there is a significant positive correlation between executive academic experience and company’s innovation ability, i.e., academics-type. There is also a significant positive correlation between the average tenure of executives and innovation ability, which still holds after robustness test. Researching the relationship between the academic experience of the executives of listed companies and their innovation ability can not only enrich the research on the characteristics of senior management team, but also provide theoretical guidance for the construction of senior management team, and provide a few suggestions for the improvement of innovation ability and the formulation of government-related policies.